Evolutionary and ecological forces influencing population diversification in Bornean montane passerines - Chua, Vivien L.; Smith, Brian Tilston; Burner, R.C.; Mustafa, Abdul Rahman; Maklarin, Lakim; Prawiradilaga, Dewi M.; Moyle, Robert G.; Sheldon, Frederick H. (Elsevier Ltd, 2017)
The mountains of Borneo are well known for their high endemicity and historical role in preserving Southeast Asian rainforest biodiversity, but the diversification of populations inhabiting these mountains is poorly studied. Here we examine the genetic structure of 12 Bornean montane passerines by comparing complete mtDNA ND2 gene sequences of populations spanning the island. Maximum likelihood and Bayesian phylogenetic trees and haplotype networks are examined for common patterns that might signal important historical events or boundaries to dispersal. Morphological and ecological characteristics of each species are also examined using phylogenetic generalized least-squares (PGLS) for correlation with population structure. Populations in only four of the 12 species are subdivided into distinct clades or haplotype groups. Although this subdivision occurred at about the same time in each species (ca. 0.6– 0.7 Ma), the spatial positioning of the genetic break differs among the species. In two species, northeastern populations are genetically divergent from populations elsewhere on the island. In the other two species, populations in the main Bornean mountain chain, including the northeast, are distinct from those on two isolated peaks in northwestern Borneo. We suggest different historical forces played a role in shaping these two distributions, despite commonality in timing. PGLS analysis showed that only a single characteristic—hand-wing index—is correlated with population structure. Birds with longer wings, and hence potentially more dispersal power, have less population structure. To understand historical forces influencing montane population structure on Borneo, future studies must compare populations across the entirety of Sundaland.